Online Learning In Elementary School During The Covid-19 Pandemic - Nita, Vera; Cahyaningsih, Agustin Atakhiroh Nur; Rachmawati, Umi (Prosiding University Research Colloquium, 2021)
Education is a conscious and planned effort made to create a learning atmosphere and learning process to provide a learning experience for students. This experience consists of 3 aspects, namely cognitive, affective and psychomotor. This research was motivated by the impact of the COVID-19 pandemic, which impacted the health and economic sectors and the education sector. Therefore, the learning process for primary school education is currently carried out remotely or online by utilizing learning media. This research is qualitative research with a case study type. The data sources were obtained from 2 research samples: the Sidorejo State Elementary School (village) and the Tempurejo 1 State Primary School (urban) from the Magelang area, which learned in the epidemic era. The technique used is the interview. The results showed that elementary schools located in cities were easier to carry out bold learning. In contrast, in village schools, the practical learning process was carried out offline, which could help students in the learning process. There were several obstacles such as unstable internet networks or even the unavailability of mobile phones to implement teaching-learning boldly.